Transition Metal-Doped Lithium Titanium Oxide Nanoparticles Made Using Flame Spray Pyrolysis. (29th December 2011) - Karhunen, T.; Lähde, A.; Leskinen, J.; Büchel, R.; Waser, O.; Tapper, U.; Jokiniemi, J.
Abstract : Defect spinel phase lithium titanate (Li4 Ti5 O12 ) has been suggested as a promising negative electrode material for next generation lithium ion batteries. However, it suffers from low electrical conductivity. To overcome this problem conduction path length can be reduced by decreasing the primary particle size. Alternatively the bulk conductivity of Li4 Ti5 O12 can be increased by doping it with a conductive additive. In this paper a steady, single-step gas-phase technique for lithium titanate synthesis that combines both approaches is described. The process is used to produce doped Li4 Ti5 O12 nanoparticles with primary particle size of only 10 nm. The product is found to consist of single-crystalline nanoparticles with high phase and elemental purity. Two dopant materials are tested and found to behave very differently. The silver dopant forms a separate phase of nanometre-sized particles of metallic silver which agglomerate with Li4 Ti5 O12 . The copper dopant, on the other hand, reacts with the lithium titanate to form a double spinel phase ofLi 3 ( Li 1 − 2 x Cu 3 x Ti 5 − x ) O 12 .